2021
DOI: 10.1002/ange.202102082
|View full text |Cite
|
Sign up to set email alerts
|

Bicyclic β‐Sheet Mimetics that Target the Transcriptional Coactivator β‐Catenin and Inhibit Wnt Signaling

Abstract: Protein complexes are defined by the three-dimensional structure of participating binding partners.K nowledge about these structures can facilitate the design of peptidomimetics which have been applied for example,a si nhibitors of protein-protein interactions (PPIs). Even though b-sheets participate widely in PPIs,t hey have only rarely served as the basis for peptidomimetic PPI inhibitors,inparticular when addressing intracellular targets.Here,wepresent the structurebased design of b-sheet mimetics targeting… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 71 publications
0
7
0
Order By: Relevance
“…25−29 Recently, Grossman and co-workers described E-cadherin β-sheet mimics to engage β-catenin. 30 Our efforts complement this work. We begin from a β-strand of a distinct protein partner (Tcf4) and focus on capturing this strand as part of a β-hairpin scaffold.…”
Section: ■ Introductionmentioning
confidence: 75%
“…25−29 Recently, Grossman and co-workers described E-cadherin β-sheet mimics to engage β-catenin. 30 Our efforts complement this work. We begin from a β-strand of a distinct protein partner (Tcf4) and focus on capturing this strand as part of a β-hairpin scaffold.…”
Section: ■ Introductionmentioning
confidence: 75%
“…Helicity values were calculated using the CDNN software tool (spectra range for calc. : 195–260 nm, , accessed on 1 January 2021) developed by G. Böhm [ 39 , 40 ].…”
Section: Methodsmentioning
confidence: 99%
“…Atomic-level characterisation of peptide:target complexes has revealed the impact of a variety of stapling chemistries on the binding modes of stapled peptides. [11], [32], [33], [34] Understanding the conformational changes induced by the staple moiety can benefit the design of new binders. While it has been shown that DVT can link i, i+7 residues on α-helical MDM2-binding peptides, the conformation of the linker and its effect on the helix geometry are unclear.…”
Section: Structural Characterisation Of Cysteine-stapled Brc8-2 Repeatsmentioning
confidence: 99%
“…[9], [10] Recently, alternative structural elements, such as βhairpins and loops have been successfully utilised for stapling. [11], [12] Stapling of the nucleophilic side chain of cysteines has been explored as an attractive alternative to RCM, as it avoids the use of non-natural amino acids and metal catalysts. [13] Stapling of cysteines can be done in mild, biocompatible conditions, allowing it to be used in the context of affinity selections of combinatorial libraries.…”
Section: Introductionmentioning
confidence: 99%